Differences in the growth stages of Erysiphe pisi on cultivars of field pea (Pisum sativum L.) - Su, H.; Hwang, S.F.; Chang, K.F.; Conner, R.L.; Howard, R.J.; Turbull, G.D.; Blade, S.F. (Springer, 2004)
The infection process of Erysiphe pisi on field pea cvs. ‘Highlight’ and ‘Tara’ carrying resistance gene erl, line ‘JI2480’ carrying resistance gene er2, and susceptible cv. ‘Radley’ (Er) was studied at 20 °C in controlled conditions. The growth stages of E. pisi were observed on these cultivars with an environmental scanning electron microscope and a light microscope. No significant differences in the number of conidia with appressoria within 12 h of incubation and in the shape of the appressoria through the 72-h incubation on all cultivars. The conidia with appressoria on cvs. ‘Highlight’ and ‘Tara’ produced little or no mycelia after 72-h incubation. The conidia on ‘JI2480’ or ‘Radley’ developed primary (Gs5) and secondary mycelia (Gs6) within 24 h of incubation, but significantly fewer conidia with appressoria developed primary or secondary mycelia on ‘JI2480’ compared to ‘Radley’ after 72-h incubation. Significant more lesions were on ‘Radley’ and ‘JI2480’ after 72-h incubation than on ‘Highlight’, but the number of lesions on ‘Tara’ was not significantly different from all these cultivars. These results show that different er genes affected different stages of the infection process of E. pisi